PENGARUH PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA SITUS JUAL BELI ONLINE ELEVENIA - Rohmah, Miftahur; Lubis, Evawani Elysa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Sales promotion is one of the elements of marketing communication that has an influence on consumer purchasing decisions. The growing number of online shopping sites in this new media era, sales promotion which is a marketing communication element has been widely used by online shopping sites. One of the online shopping sites is Elevenia, is an online shop that quite often do sales promotion. The theory used in this research is S-R theory. The purpose of this study is to find out how much influence sales promotion of consumer purchasing decisions online sales sites Elevenia.This study uses quantitative research methods, with data collection techniques that is through a questionnaire using google docs online to consumers online sale and purchase sites Elevenia with a sample of 96 which is determined through the unknow population calculation. Data analysis technique in this research using explanation technique intended to explain a generalization of sample to its population or explain relationship, difference, or influence of a variable with others.Based on these results, the influence of sales promotion on consumer purchasing decision Elevenia online sale sites obtained regression coefficient value in this study is Y = 17.286 + 0.542 X the constant number (a) of 17.286 and the coefficient of keputsan 0.542 while t count 7,400 bigger if in comparison with t table 1.986, with a significance level of 0.000 smaller than Î± = 0.05. That is, there is the influence of sales promotion on consumer purchasing decisions online sales sites Elevenia. From the calculation results obtained coefficient of determination (R2) of 0.368, which implies that the influence of free variables (sales promotion) to the dependent variable (purchase decision) is equal to 36.8% with low category, while the remaining 63.2% other factors beyond the variables studied. which is not mentioned in this study, thus Ha is rejected and Ho accepted.Keywords: Sales Promotion, Consumer Purchasing Decisions, Elevenia Online Site